Microcontroller ATMega328 -Based Alcohol Danger Warning System of Ethanol Based on Detection of Alcohol Content in the Breath - La Ode Hamrin Hamury (STIKes Mandala Waluya Kendari, 2019)
Today, the number of social problems in the community arising from the use of ethanol is quite disturbing. Drinks containing ethanol are widely circulated in Indonesia. The consumption of alcoholic beverages is well known and has become prevalent and accepted in social relationships. This paper is a development and realization of alcohol measuring devices in breath. The alcohol detector used in this tool is the MQ3 gas sensor. Data detected by thesensor from the breath was processed and identified by the ATMega328 microcontroller. Identification of conditions related to the alcohol levels was displayed on the LCD. The alcohol content that can be detected by this tool is 0.01% BAC-0.20% BAC. Program instructions contained in the microcontroller are categorized under 3 conditions, which are safe, alert, and dangerous. Testing of equipment is carried out on alcohol samples in several containers with different levels. The results showed that an alcohol levelof 0.01% -0.05% has a safe status, an alcohol content of 0.06% 0.10 has an alert status, and an alcohol content of 0.11% -0.20% has a dangerous status. The value of the content along with the description according to the condition was displayed digitally. This tool can measure the level of alcohol through the breath and displays the status level of the alcohol content in the breath. This tool is suitable for detecting whether someone is an alcoholic or not. The type of alcohol that can be detected by this tool is ethanol.